A STUDY ON KNOWLEDGE MANAGEMENT AND ITS IMPACT ON ORGANISATIONAL PERFORMANCE IN INDIAN CORPORATE SECTORS - EVANGELIN, MS.M. RUBY; RAMPRABHA, K. (International Journal of Psychosocial Rehabilitation, 2020)
In this competitive world, Knowledge Management (KM) plays an important role in enhancing the organization to achieve the competitive advantage and organizational success. Hence it is necessary to view the impact of KM on the growth of the organizations, especially in corporate sectors. To our knowledge, KM practices have implemented in the majority of the sectors like banking, hotel and some corporate sectors, however, the in-depth research towards the impact of KM on corporate sectors growth is restricted. Therefore, the present study intends to represent a holistic approach via study the impact of KM practices on Indian corporate sectors through secondary data collection. Further, the study analyses the importance, components of KM and its models and application in Indian corporate sectors. From this, the study findings highlighted that how KM practices impact and enhance the organizational growth in Indian corporate sectors. KM practices provide growth to the organization but also face some challenges at the time of execution. Hence the present study gives recommendations to stakeholders in the corporate sectors in order to overcome the problems that arise from the implementation of KM practices in India. In addition, this study contributes to the KM field by find out the influence of KM practices on corporate sector growth in India, not only corporates but also give suggestions to other sectors as well.